A rare loss-of-function genetic mutation suggest a role of dermcidin deficiency in hidradenitis suppurativa pathogenesis - Tricarico, Paola Maura; Gratton, Rossella; Santos-Silva, Carlos André dos; Moura, Ronald Rodrigues de; Ura, Blendi; Sommella, Eduardo; Campiglia, Pietro; Del Vecchio, Cecilia; Moltrasio, Chiara; Berti, Irene; D’Adamo, Adamo Pio; Elsherbini, Ahmed M. A.; et al. (Frontiers in Immunology, 2022)
Hidradenitis suppurativa (HS) is a chronic inflammatory skin disease with a multifactorial aetiology that involves a strict interplay between genetic factors, immune dysregulation and lifestyle. Familial forms represent around 40 % of total HS cases and show an autosomal dominant mode of inheritance of the disease. In this study, we conducted a whole-exome sequence analysis on an Italian family of 4 members encompassing a vertical transmission of HS. Focusing on rare damaging variants, we identified a rare insertion of one nucleotide (c.225dupA:p.A76Sfs*21) in the DCD gene encoding for the antimicrobial peptide dermcidin (DCD) that was shared by the proband, his affected father and his 11-years old daughter. Since several transcriptome studies have shown a significantly decreased expression of DCD in HS skin, we hypothesised that the identified frameshift insertion was a loss-of-function mutation that might be associated with HS susceptibility in this family. We thus confirmed by mass spectrometry that DCD levels were severely diminished in the affected members and showed that the antimicrobial activity of a synthetic DCD peptide resulting from the frameshift mutation was impaired. In order to define the consequences related to a decrease in DCD activity, skin microbiome analyses of different body sites were performed by comparing DCD mutant and wild type samples, and results highlighted significant differences between the groins of mutated and wild type groups. Starting from genetic analysis conducted on an HS family, our findings showed, confirming previous transcriptome results,, the potential role of the antimicrobial DCD peptide as an actor playing a crucial part in the etio-pathogenesis of HS and in the maintenance of the skin’s physiological microbiome composition; so, we can hypothesise that DCD could be used as a novel target for personalised therapeutic approach.